(untitled) (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
The present text has the objective of mapping the lines present in the research project "Traces of the common, alternative bodies and other forms of survival: literature, cultural and political field in Portuguese language contexts", which I coordinate in the PUC-Rio. A comparative analysis of literary texts and cultural objects produced in Portugal, Angola, Mozambique and Brazil, aims to examine the specific characteristics of this cultural field, with emphasis on the cohabitation of knowledge considered superior and subordinate knowledge in the course of colonial modernity. The investigation comprises literary and cultural objects produced from different epistemic matrices, considered gestures of recognition of alterity and diversity, structuring the societies in question.